Manajemen Pendidikan Islam dalam Konteks Moderasi Beragama di Indonesia - Fahmi Hauzan Rafif; Muhammad Faiq Haqqoni; Fahmi Firmansyah; Dirgantara Wicaksono (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The growing global trends of religious polarization, intolerance, and extremism have positioned education as a strategic arena for strengthening religious moderation. Indonesia, characterized by its plural Muslim society and long-standing tradition of Islamic wasathiyah, is frequently regarded as a significant reference in the implementation of religious moderation through education. However, existing studies largely emphasize normative and curricular dimensions, while managerial and governance aspects of Islamic education remain underexplored. This article aims to critically examine how religious moderation is integrated into the management functions of Islamic education and to propose a conceptual framework for moderate Islamic education management. Employing a qualitative approach through a systematic qualitative literature review, this study analyzes reputable academic publications and relevant policy documents. Data were examined using the Planning, Organizing, Actuating, and Controlling (POAC) framework as the primary analytical lens. The findings indicate that religious moderation can be operationalized as an integrated managerial principle embedded in policy planning, organizational structuring, program implementation, and evaluative mechanisms. This study contributes theoretically by positioning religious moderation as a managerial paradigm within Islamic education management and offers practical implications for developing inclusive, sustainable, and context-responsive governance of Islamic education in multicultural societies.